2005
DOI: 10.1158/0008-5472.can-05-0424
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Damage Mediates Genotoxicity of Arsenic in Mammalian Cells

Abstract: Arsenic is an important environmental carcinogen that affects millions of people worldwide through contaminated water supplies. For decades, arsenic was considered a nongenotoxic carcinogen. Using the highly sensitive A L mutation assay, we previously showed that arsenic is, indeed, a potent gene and chromosomal mutagen and that its effects are mediated through the induction of reactive oxygen species. However, the origin of these radicals and the pathways involved are not known. Here we show that mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 61 publications
7
113
0
Order By: Relevance
“…ROS may have a multifactorial origin, mitochondria being one of the possible sources. Arsenic, a well characterized and common carcinogen, damages mitochondria and promotes mitochondrial ROS production (237,238), and the carcinogen benzo(a)pyrene induces mitochondrial dysfunction (239). Importantly, the accumulation of mutations in people not exposed to carcinogens is associated with the presence of peroxidized lipids.…”
Section: Cancer and Ageing 621 Cancermentioning
confidence: 99%
“…ROS may have a multifactorial origin, mitochondria being one of the possible sources. Arsenic, a well characterized and common carcinogen, damages mitochondria and promotes mitochondrial ROS production (237,238), and the carcinogen benzo(a)pyrene induces mitochondrial dysfunction (239). Importantly, the accumulation of mutations in people not exposed to carcinogens is associated with the presence of peroxidized lipids.…”
Section: Cancer and Ageing 621 Cancermentioning
confidence: 99%
“…In the present studies, we investigated the nature of the DSB-inducing factor(s) and how it was generated and transferred. By treating the cells with L-NMMA to inhibit the NOS activity (Leach et al, 2002;Liu et al, 2005) (D-NMMA), it was found that L-NMMA, could effectively block the DIA of conditioned medium in the receptor cells. In contrast, D-NMMA, the inactive enantiomer had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…The conditioned medium collected at 10 min post 1 cGy a-particle irradiation was transferred to the medium receptor cells. L-NMMA (Molecular Probes, Eugene, Oregon, USA) has been shown to be an effective NOS inhibitor (Leach et al, 2002;Liu et al, 2005). However, in the presence L-NMMA, the conditioned medium collected at 10 min post-irradiation showed no distinct DIA (15.7-15.1%, P ¼ 0.83) (Figure 1), whereas only a marginal decrease (29.6-26.0%) in DIA was found with D-NMMA Figure 1 Effect of the NOS inhibition, L-NMMA (a NOS inhibitor, 1 mM), D-NMMA (non-reactive D-enantiomer, 1 mM), 7-Ni (a selective cNOS inhibitor, 4 mM) or AG (a selective iNOS inhibitor, 0.1 mM) on the induction of bystander DSBs.…”
Section: No Mediates the Dsbs Induction In Bystander Normal Human Skimentioning
confidence: 99%
“…5,6 In mammal cells, arsenic genotoxicity is mainly mediated by mitochondrial damage, including mitochondrial oxidative dysfunction. 7,8 Here we report a patient with APL who developed a delayed, severe, and partially reversible mitochondrial myopathy after being treated with ATO. …”
mentioning
confidence: 95%